Structure and Development of Rabies Virus in Tissue Culture - Hummeler, Klaus (1967)
Structure and development of two fixed rabies virus strains in baby hamster kidney cells (BHK/21) were investigated by electron microscopy. The morphological development was correlated with fluorescent-antibody staining and infectivity titration. The uptake of virus was enhanced by addition of diethylaminoethyl dextran, and structural changes became apparent in the cytoplasm 8 to 9 hr after infection, when fluorescent-antibody staining was first discernible. These changes consisted of matrices containing fibers replacing normal cytoplasmic structures. Virus particles appeared at the edges of these matrices and inside them at 24 to 48 hr. This corresponded to significant rises in intracellular infectious virus. Formation of virus particles by budding from cell membranes was seen at 72 hr. Further incubation of the infected cells resulted in synthesis of bizarre structural elements. The complete virus particle was bullet-shaped with an average size of 180 by 75 mμ. It consisted of an inner core of filamentous material surrounded by two membranes of different densities. The surface showed a honeycomb arrangement with surface protrusions 60 to 70 A long having a knoblike structure at their distal end. These surface protrusions were absent at the flat end of the virus particle.